Organic-inorganic mutually-embedded space structure AAO / PVDF composite coating and preparation method thereof

By preparing an AAO/PVDF composite coating with an organic-inorganic inter-embedded space structure on the surface of the aluminum alloy, the problems of insufficient interface bonding strength and poor anti-shrink corrosion performance in the prior art are solved, and efficient and long-term anti-corrosion and pollution resistance are achieved, and green and environmentally friendly in the marine environment.

CN119710861APending Publication Date: 2025-03-28SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411881360.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing eco-friendly organic anti-fouling coatings have problems in marine engineering applications, such as insufficient interface bonding strength, poor resistance to mechanical damage and anti-shrink corrosion. Their use in marine environments will lead to the release of heavy metal ions and pollute the marine environment.

Method used

AAO/PVDF composite coating with organic-inorganic inter-embedded space structure was prepared on the surface of aluminum alloy using hard template-soft modification technology. PVDF was filled in the nanopores of anodized aluminum through a vacuum solution casting process, and a coating with piezoelectric characteristics was obtained by high-voltage polarization treatment.

Benefits of technology

It has achieved high interface bonding strength, good corrosion resistance, mechanical damage resistance and long-term anti-corrosion and anti-fouling performance, and stimulates piezoelectric effect through environmental disturbance in the marine environment, inhibits bacterial adhesion, and is green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710861A_ABST
    Figure CN119710861A_ABST
Patent Text Reader

Abstract

The invention discloses an organic-inorganic mutually-embedded space structure AAO / PVDF composite coating and a preparation method thereof, based on a hard template-soft modification technology, a hard porous anodic oxidation aluminum oxide layer is obtained on the surface of an aluminum alloy; injecting a polyvinylidene fluoride (PVDF) solution into the nano pore channels of the anodic aluminum oxide layer through a vacuum pressure impregnation process and a solution casting method, curing to form a nano column array structure, and performing high-pressure polarization treatment on PVDF nano columns by adopting a corona polarization mode; and the antibacterial, antifouling and anticorrosive AAO / PVDF composite coating based on environment excitation charge response of the piezoelectric effect can be prepared. The AAO / PVDF coating disclosed by the invention has excellent antibacterial property, strong interface bonding and stable piezoelectric property, and PVDF effectively seals nano pore channels of AAO, so that the anti-corrosion property of the aluminum alloy is remarkably improved, and the anti-corrosion and anti-fouling process has the characteristics of being long-acting, environment-friendly and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preventing marine biological fouling on aluminum alloy surfaces, and specifically, to PVDF soft modification of hard anodized aluminum based on a hard template-soft modification technology, and relates to a long-lasting anti-corrosion and anti-fouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure and a preparation method thereof, which has long-lasting anti-corrosion, anti-fouling and antibacterial properties. Background Art

[0002] Lightweight, corrosion-resistant aluminum alloys are expected to partially replace steel materials commonly used in ships and marine engineering, and can potentially be used as offshore platform oil and gas drilling equipment, port fixed structures, and ship structures. However, aluminum alloys face serious marine biofouling and corrosion problems when in long-term contact with seawater. Aluminum alloys corrode significantly in seawater environments, and marine biofouling accelerates aluminum alloy corrosion, shortens the service life of aluminum alloy parts, affects the safe operation of equipment systems, and increases the maintenance cost of facilities. Therefore, marine biofouling and corrosion of aluminum alloys in marine environments are engineering problems that need to be solved urgently.

[0003] It is generally recognized that the matrix film induced by the adhesion of marine microorganisms is a key factor in the evolution and development of marine biofouling on the surface of materials. Effectively inhibiting the adhesion of microorganisms such as bacteria and fungi on the surface of materials and controlling the formation of initial matrix film fouling have become recognized methods to prevent marine biofouling. The existing mainstream anti-fouling methods mainly regulate the surface morphology and functional components of materials to give the material surface the property of inhibiting bacterial adhesion. For example, organic coatings containing antifouling agents or bactericides are applied to the surface of materials, and toxic agents are used to control the adsorption of bacteria and microorganisms to form an initial matrix film, thereby eliminating or inhibiting the key process of marine biofouling formation. This is the most common technology in actual engineering applications. However, the interfacial bonding strength between organic antifouling coatings and metal substrates is weak, and surface fouling needs to be cleaned regularly and the organic coating needs to be reapplied. The maintenance process is cumbersome and costly, and there are certain limitations on the performance requirements of organic antifouling coatings such as resistance to mechanical damage and erosion corrosion. On the other hand, heavy metal ions released into seawater by organic antifouling coatings seriously affect the marine environment and organisms. The concentration of heavy metal elements in seabed mud seriously exceeds the standard. Free heavy metal ions can cause genetic variation and abnormal development of marine organisms and enter the human body through the food chain. In recent years, the marine environmental problems caused by various heavy metal ions released by organic antifouling coatings are very significant. The International Maritime Organization calls for full consideration of the pollution and damage of antifouling agents to the marine ecological environment. The use of organic tin compounds in antifouling coatings has been banned. The development of green and long-lasting anticorrosion and antifouling coatings has become the future development trend of marine biofouling prevention and control.

[0004] At present, a large number of studies have developed various coatings from the eco-friendly perspective of antifouling coatings, such as the laboratory microbiological experiment of super hydrophobic surface has good results (see Chinese patent, application number CN202410848829.0), but the performance is still insufficient in the marine field hanging board test, low surface energy organic matter is easy to degrade, and the brittle hydrophobic network structure cannot withstand harsh mechanical damage and fluid scouring damage. The self-polishing antifouling coating released by dynamic dissolution (see Chinese patent, application number CN202410660043.6, CN202411010200.5) shows good antifouling effect in laboratory microbiological experiments and marine field hanging board tests, but the long-term antifouling property and mechanical damage resistance of the coating exposed in the actual service process are still not up to expectations, the surface antifouling performance of the organic coating drops sharply after being scratched or worn, the dynamic dissolution rate is difficult to stably control, the interface bonding strength between the organic coating and the substrate is still insufficient, and the service use of the organic antifouling coating lacks long-term effectiveness. High interface bonding strength, mechanical damage resistance and long-term effectiveness have become bottleneck issues in the application of antifouling coatings in the field of marine engineering. Therefore, it is of urgent practical significance to explore the design methods of new long-term anticorrosion and antifouling coatings on the surface of aluminum alloys for marine engineering applications. Summary of the invention

[0005] In view of the shortcomings of existing eco-friendly organic antifouling coatings, the purpose of the present invention is to provide a method for preparing a long-term anticorrosion and antifouling AAO / PVDF composite coating with an organic-inorganic intercalated spatial structure based on a hard template-soft modification technology. Utilizing the nanoporous structure of hard anodized aluminum, PVDF is filled into the nanopores of anodized aluminum through a vacuum solution casting process, and an organic-inorganic intercalated spatial structure is formed after solidification. After high-voltage polarization, a long-term anticorrosion and antifouling AAO / PVDF composite coating with piezoelectric properties is obtained. The coating can utilize environmental disturbances to spontaneously induce the generation and release of surface charges to interact with bacteria, inhibiting the formation of bacterial matrix membranes on the surface of aluminum alloys. The AAO / PVDF composite coating has the advantages of high interface bonding strength, good corrosion resistance, resistance to mechanical damage and good long-term performance. The antibacterial and antifouling process is green and environmentally friendly, and can be potentially applied to the field of marine biological fouling prevention and anticorrosion technology for aluminum alloys facing marine engineering.

[0006] Most bacteria have charged groups on their surfaces, and giving the material surface charge characteristics can affect the adhesion behavior of bacteria on the material surface. Based on the principle of interaction between bacteria and charge, designing the charge characteristics of the aluminum alloy surface can effectively inhibit the adhesion of bacterial microorganisms. The main methods of charging the material surface are friction charging, contact charging and induction charging. Induction charging of materials in the marine environment is the most feasible technology. Piezoelectric materials are typical induction charging materials. The marine environment disturbance can be used to stimulate the dynamic response of the piezoelectric coating surface to generate induced charges. Polyvinylidene fluoride (PVDF) is one of the most typical piezoelectric materials. It has a series of advantages such as material flexibility, low density, corrosion resistance, wear resistance, impact resistance and aging resistance. The molding process of PVDF is simple. Therefore, PVDF organic piezoelectric coating can be prepared on the aluminum alloy surface. The piezoelectric characteristics of PVDF coating can be used to inhibit the adhesion of bacteria on the aluminum alloy surface, thereby controlling the marine biological fouling on the aluminum alloy surface.

[0007] The present invention provides a method for preparing a long-lasting anti-corrosion and anti-fouling coating on an aluminum alloy surface based on the piezoelectric effect. The method uses an anodizing process to construct an anodized aluminum oxide AAO having a nanoporous structure on the aluminum alloy surface, and then uses a vacuum solution casting process to fill the nanopores of the anodized aluminum layer with PVDF. The AAO / PVDF composite coating has significant piezoelectric response characteristics after high-voltage corona polarization. The present invention proposes a hard template-soft modification process for PVDF soft modification of hard anodized aluminum. The method is used to prepare an anti-corrosion and anti-fouling AAO / PVDF composite coating having the following characteristics: ① PVDF seals the nanopores of the AAO coating, which can effectively prevent chloride ions in seawater from penetrating into the bottom of the AAO coating to corrode the aluminum substrate. The chemical properties of PVDF itself are extremely stable and resistant to seawater corrosion. The AAO / PVDF composite coating has excellent corrosion resistance. ② The nanopores provide a large number of interfaces between PVDF and AAO, significantly improving the interfacial bonding strength between PVDF and aluminum alloy, and well solving the problem of organic ③ The hard and wear-resistant AAO coating has good resistance to mechanical damage and fluid erosion, which can prevent the flexible PVDF coating from being damaged by external mechanical forces and wearing out too quickly. The piezoelectric PVDF nanocolumn array in the nanochannel can still achieve the long-term function of inhibiting bacterial adhesion of the coating; ④ With the help of ocean waves and seawater impact disturbances, the piezoelectric PVDF is continuously stimulated by external forces to induce the formation and release of surface charges, thereby effectively inhibiting the fouling of marine organisms on the surface of aluminum alloys. The environmentally stimulated charge response antibacterial process has significant green and environmental protection characteristics for the marine environment.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a long-lasting anticorrosion and antifouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure based on a hard template-soft modification technology, comprising the following steps:

[0010] S1. Anodizing treatment: Anodizing the aluminum alloy substrate in an electrolyte to obtain an anodized aluminum layer, and then performing pore expansion treatment to enlarge the nanopore diameter of the anodized aluminum layer;

[0011] S2, vacuum solution casting: vacuum degassing the anodized aluminum layer obtained in step S1, and then fully filling the PVDF solution into the nanopores of the anodized aluminum layer under high-purity nitrogen pressure treatment, and then performing PVDF curing treatment after filling;

[0012] S3. Corona polarization treatment: The cured anodized aluminum layer is subjected to corona polarization treatment to obtain an AAO / PVDF composite coating having an organic-inorganic intercalated structure with piezoelectric properties.

[0013] As some specific embodiments of the present invention, in step S1, the aluminum alloy substrate must undergo pretreatment before anodizing, specifically including: grinding, polishing and ultrasonic cleaning the aluminum alloy, then removing surface organic matter and oxide layer by alkaline washing and acid washing, and performing electrochemical polishing in a solution containing perchloric acid to obtain an aluminum alloy substrate in a reflective mirror state.

[0014] As some specific embodiments of the present invention, the polishing is to polish the aluminum alloy using 180#, 400#, 800#, 1500# and 3000# SiC waterproof sandpaper in sequence;

[0015] The polishing comprises sequentially using diamond polishing liquids with particle sizes of 9 μm, 3 μm and 1 μm to polish the ground aluminum alloy for 2-5 minutes;

[0016] The ultrasonic cleaning is to ultrasonically clean the ground and polished aluminum alloy in acetone, pure water and ethanol respectively for 3-5 minutes.

[0017] As some specific embodiments of the present invention, the alkali solution used for alkali washing is a 25-40g / L NaOH solution; the acid solution used for pickling is a HNO3 solution with a mass fraction of 20-25%; the alkali washing time is 3-5min, and organic matter on the surface of the aluminum alloy is removed by alkali washing; the pickling time is 5-10min, and surface oxides and residual alkali solution are removed by pickling.

[0018] As some specific embodiments of the present invention, the electrochemical polishing is carried out in a perchloric acid / ethanol electrolyte under a DC voltage of 20-25V and a water bath condition of 0-5°C; the electrochemical polishing time is 4-10min, and an aluminum alloy substrate in a reflective mirror state is obtained after polishing; in the electrolyte, the volume ratio of HClO4 and C2H5OH is 1:3-1:5.

[0019] Preferably, the volume ratio of HClO4 and C2H5OH solution is V1:V2=1:4.

[0020] As some specific embodiments of the present invention, the step of pretreating the aluminum alloy substrate specifically includes: polishing with 180#, 400#, 800#, 1500# and 3000# SiC waterproof sandpaper in sequence, polishing with 9μm, 3μm and 1μm diamond polishing liquid for 2-5min in sequence after polishing, and ultrasonically cleaning in acetone, pure water and ethanol for 3-5min in sequence after polishing; immersing the cleaned aluminum alloy in alkali solution and acid solution to remove surface organic matter and oxide layer, and then ultrasonically cleaning in acetone, pure water and ethanol for 3-5min in sequence, electrochemically polishing the aluminum alloy in perchloric acid / ethanol electrolyte at 20-25V DC voltage and 0-5℃ water bath conditions for 4-10min, finally obtaining an aluminum alloy in a reflective mirror state, and then ultrasonically cleaning in acetone, pure water and ethanol for 3-5min in sequence, and blowing dry with cold air for standby use.

[0021] As some specific embodiments of the present invention, in step S1, during the anodizing treatment, the aluminum alloy substrate is used as the anode working electrode, the inert conductive electrode is used as the cathode, and the anodized aluminum alloy is treated at a constant pressure in an acidic electrolyte and a constant temperature water bath for 15-60 minutes.

[0022] As some specific embodiments of the present invention, the inert conductive electrode includes at least one of a carbon plate, a titanium plate, a platinum plate, and a gold plate.

[0023] As some specific embodiments of the present invention, the acidic electrolyte is at least one of phosphoric acid, sulfuric acid, and oxalic acid solutions.

[0024] As some specific embodiments of the present invention, the acidic electrolyte is a phosphoric acid solution, the mass fraction of the phosphoric acid solution is 5-20%, the constant temperature water bath temperature is 15-25°C, the voltage is 40-70V, and the time is 15-45min;

[0025] And / or, the acidic electrolyte is a sulfuric acid solution, the mass fraction of the sulfuric acid solution is 10-20%, the constant temperature water bath temperature is 0-5°C, the voltage is 20-35V, and the time is 15-45min;

[0026] And / or, the acidic electrolyte is an oxalic acid solution, the mass fraction of the oxalic acid solution is 3-10%, the constant temperature water bath temperature is 0-5°C, the voltage is 40-65V, and the time is 20-60min.

[0027] Preferably, the acidic electrolyte is a phosphoric acid solution, the mass fraction of the phosphoric acid solution is 15%, the temperature of the constant temperature water bath is 20°C, the voltage is 50-60V, and the time is 30min;

[0028] And / or, the acidic electrolyte is a sulfuric acid solution, the mass fraction of the sulfuric acid solution is 15%, the temperature of the constant temperature water bath is 0°C, the voltage is 25-30V, and the time is 30min;

[0029] And / or, the acidic electrolyte is an oxalic acid solution, the mass fraction of the oxalic acid solution is 5%, the temperature of the constant temperature water bath is 0° C., the voltage is 50-60V, and the time is 60 minutes.

[0030] As some specific embodiments of the present invention, in step S1, the solution used for the pore expansion treatment is a phosphoric acid solution with a mass fraction of 3-5%, the pore expansion treatment time is 5-30 minutes, and the temperature is 40-60° C. Through the pore expansion treatment, the rate of PVDF solution infiltration into the AAO nanopores is accelerated, and the preparation time of the vacuum-pressure solution casting process is reduced.

[0031] As some specific embodiments of the present invention, in step S2, the PVDF solution is prepared by dissolving PVDF powder in an organic solvent, the mass fraction of PVDF in the PVDF solution is 30-70%, and the organic solvent is N,N-dimethylformamide (DMF).

[0032] Specifically, PVDF powder is dissolved in DMF by magnetic stirring at a speed of 50-300 rpm for 1-3 hours.

[0033] As some specific embodiments of the present invention, in step S2, the vacuum degassing and high-purity nitrogen pressurization steps are carried out in a high-pressure tank. During the vacuum degassing, the high-pressure tank is first evacuated to 0-0.1 bar and maintained for 1-2 minutes, and then the PVDF solution is contacted with the anodized aluminum layer under 0-0.1 bar conditions and maintained for 10-60 minutes; high-purity nitrogen is introduced and pressurized to 10 6 -10 7 bar, and maintain for 20-60 minutes. The air in the nanopores of the anodized aluminum is discharged through vacuum degassing. First, vacuum is drawn, and then the anodized aluminum is contacted with the PVDF solution under vacuum, which can fully discharge the air in the pores, making the resistance of PVDF entering the pores smaller, and then high-purity nitrogen is introduced for pressurized treatment, so that PVDF can fully fill the nanopores of the anodized aluminum.

[0034] In some specific embodiments, the anodized aluminum is fixed to the sealing cover of the austenitic stainless steel tank body with two magnets, one magnet is placed on the outer surface of the sealing cover, and the other magnet is placed on the inner surface of the sealing cover and the anodized aluminum is sandwiched between the magnet and the sealing cover. After the PVDF / DMF solution is poured into the tank body, the tank body is sealed, and the tank body is evacuated until the pressure gauge shows 0.1 bar and maintained for 1-2 minutes, and then the air valve connected to the vacuum pump is closed, and then the outer magnet of the sealing cover is removed to make the anodized aluminum fall into the PVDF / DMF solution, and maintained below 0.1 bar for 10-60 minutes. This step can discharge the air in the nanopores of the anodized aluminum layer, and then the air valve connected to the high-purity nitrogen cylinder is opened, and nitrogen is injected until the pressure gauge shows 10 6 bar, close the valve connected to the high-purity nitrogen cylinder, and 6 The bar is maintained above 20-60 minutes. The entire treatment process allows the PVDF / DMF solution to fully enter the nanopores of the anodized aluminum for filling.

[0035] As some specific embodiments of the present invention, in step S2, the curing treatment is carried out in an oven or a heat treatment furnace. During the curing treatment, the material is first kept at 60-80°C for 1-3 hours, and then kept at 110-140°C for 3-8 hours.

[0036] As some specific embodiments of the present invention, in step S3, during the corona poling treatment, the electric field strength is 3-10kV / cm, the polarization time is 30-60min, and the voltage polarization is carried out in a high-voltage polarization device; during the corona poling, the voltage and the distance between the high-voltage needle tip and the anodized aluminum can be adjusted, the corona poling voltage is 4-20kV, and the distance between the needle tip and the surface of the anodized aluminum is 3-15mm.

[0037] Preferably, the electric field strength is 10 kV / cm, the corona polarization voltage is 10 kV, and the distance between the high-voltage needle tip and the anodized aluminum is 10 mm.

[0038] As some specific embodiments of the present invention, the needle tip of the corona polarization can be selected from a single needle structure and a multi-needle array structure. The polarization voltage and the spacing between the needle tip and the anodized aluminum of the multi-needle array structure are set the same as those of the single needle. The spacing of the multi-needle array structure is 5-10mm, and the arrangement of the multi-needle array structure is designed according to the area of ​​the aluminum alloy. For example, a square aluminum alloy of 50mm×50mm can adopt a multi-needle array structure, which can be an array structure formed by 9 single needles of 3×3.

[0039] Preferably, the needle tip for corona polarization is a multi-needle array structure formed by a combination of 9 single needles in a 3×3 arrangement, the polarization voltage of the multi-needle array structure is set to 10 kV, the distance between the needle tip and the anodized aluminum is 10 mm, the electric field strength is 10 kV / cm, and the needle tip spacing of the array structure is 5 mm.

[0040] In a second aspect, the present invention provides an AAO / PVDF composite coating having an organic-inorganic intercalated structure with piezoelectric properties, which is prepared by any of the methods described above.

[0041] Invention patent CN104959045B discloses a method for preparing polyvinylidene fluoride nano-array porous membrane, in which PVDF is prepared on anodized aluminum, specifically, a PVDF solution is dripped into the nano-pores of anodized aluminum at room temperature and pressure, and the surface PVDF solution is blown off with nitrogen after dripping to expose the anodized aluminum. The purpose is to use the nano-pores of anodized aluminum as a template to synthesize a PVDF nano-array porous membrane. When this method is used to prepare a PVDF nano-array porous membrane, it is difficult for the PVDF solution to fully enter the nano-pores of anodized aluminum for filling, and it is impossible to form a PVDF nano-column with high integrity, nor to form a spatial structure of organic and inorganic intercalation, and it does not have corrosion resistance.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The present invention prepares a long-lasting anti-corrosion and anti-fouling AAO / PVDF composite coating on the surface of aluminum alloy based on the hard template-soft modification technology. The coating can use the dynamic disturbance pressure of the environment to continuously induce the generation and release of charges on the surface of the PVDF piezoelectric coating, reduce the adhesion of bacteria on the surface of the aluminum alloy, and then inhibit the formation of marine biofouling. The antibacterial and antifouling process of the PVDF piezoelectric coating will not release toxic substances that affect marine life and the ecological environment, and has significant eco-friendly characteristics.

[0044] (2) The present invention utilizes the nanoporous structure of hard anodized aluminum to fill PVDF, forming an organic-inorganic intercalated spatial structure between the aluminum alloy substrate and the PVDF coating, which greatly improves the interface bonding strength between the organic PVDF piezoelectric coating and the aluminum alloy, and ingeniously solves the problem of weak organic-inorganic interface bonding.

[0045] (3) PVDF fills the nanopores of anodized aluminum, effectively preventing corrosive chloride ions in seawater from corroding the aluminum alloy substrate. The PVDF coating has stable chemical properties and is corrosion-resistant, ensuring the superior corrosion resistance of the AAO / PVDF composite coating.

[0046] (4) Hard and wear-resistant anodized aluminum has good resistance to mechanical damage and fluid erosion, ensuring that after the PVDF coating is peeled off or broken by severe mechanical force, the PVDF nanocolumn array embedded in the nanopores can still maintain a stable piezoelectric effect, realizing the long-term effectiveness of the AAO / PVDF composite coating in inhibiting bacterial adhesion and anti-corrosion functions. This mutually embedded structure has such an effect, and the PVDF / AAO composite coating has both antibacterial and anti-corrosion functions integrated. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0048] Figure 1 Schematic diagram of the structure of AAO / PVDF composite coating formed on aluminum substrate;

[0049] Figure 2 It is a schematic diagram of the process of vacuum pressure solution casting;

[0050] Figure 3 This is a cross-sectional SEM morphology image of the AAO / PVDF composite coating of Example 1;

[0051] Figure 4 The SEM morphology images of the surface coatings of Comparative Examples 1-3 and Examples 2-4;

[0052] Figure 5 XRD phase structure spectra of Comparative Example 2 and Examples 2-4;

[0053] Figure 6 is the piezoelectric coefficient d after corona poling of Comparative Example 2 and Examples 2-4 33 Result graph;

[0054] Figure 7 Macroscopic photos of the coating plate experiments of planktonic Escherichia coli and Staphylococcus aureus of the composite coatings in Comparative Examples 1-2 and Examples 2-4;

[0055] Figure 8 The SEM morphology of bacterial adhesion of Escherichia coli and Staphylococcus aureus adhered to the surface of the composite coating in Comparative Examples 1-2 and Examples 2-4;

[0056] Fig. 9 The electrochemical curves and immersion corrosion morphologies of the aluminum substrate, comparative examples 1, 3, and example 4 are shown. DETAILED DESCRIPTION

[0057] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0058] Example 1

[0059] This embodiment provides a method for preparing a long-term anticorrosion and antifouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure based on a hard template-soft modification technology, comprising the following steps:

[0060] (1) Aluminum alloy pretreatment:

[0061] The 6061 aluminum alloy with a size of 50 mm × 50 mm was polished with 180#, 400#, 800#, 1500# and 3000# SiC waterproof sandpapers in turn. When replacing sandpapers with different meshes, the aluminum alloy polishing direction was rotated 90°. After polishing, diamond polishing liquid with particle sizes of 9μm, 3μm and 1μm was used for polishing for 2 minutes, and then ultrasonically cleaned in acetone, pure water and ethanol for 3 minutes.

[0062] The cleaned aluminum alloy was immersed in a 30 g / L NaOH solution for 3 min to remove surface organic matter, then immersed in a 25% by mass HNO3 solution for 5 min to remove surface oxides and residual alkali solution, and then ultrasonically cleaned with acetone, pure water and ethanol for 3 min.

[0063] In an electrolyte of HClO4 and C2H5OH with a volume ratio of 1:3, electrochemical polishing was carried out at a DC voltage of 20 V and a water bath at 0°C for 5 min, and then ultrasonically cleaned in acetone, pure water and ethanol for 3 min and dried with cold air.

[0064] (2) Anodizing treatment:

[0065] The carbon plate was used as the cathode, the pretreated aluminum alloy substrate was used as the anode working electrode, and a 5% by mass oxalic acid solution was used as the electrolyte. In a constant temperature water bath at 0°C, a constant voltage of 60V was applied to anodize the aluminum alloy substrate for 60 minutes; the anodized aluminum was rinsed with pure water, and then the anodized aluminum was placed in a 5% by mass phosphoric acid solution for pore expansion for 30 minutes, and the solution temperature was 50°C.

[0066] (3) Vacuum solution casting:

[0067] The PVDF powder was dissolved in DMF by magnetic stirring at a speed of 150 rpm for 2 h to obtain a PVDF solution with a mass fraction of 70%.

[0068] One magnet is placed on the outer surface of the sealing cover of the austenitic stainless steel tank body, and another magnet is placed on the inner surface of the sealing cover and the anodized aluminum is sandwiched between the magnet and the sealing cover, so that the anodized aluminum is fixed on the sealing cover of the austenitic stainless steel tank body by two magnets, and the PVDF solution is poured into the tank body.

[0069] like Figure 2 As shown, first evacuate the tank to a vacuum degree below 0.1 bar, keep it for 1 minute, then close the valve connected to the vacuum pump, then remove the outer magnet of the sealing cover to make the anodized aluminum fall into the PVDF / DMF solution, keep it below 0.1 bar for 30 minutes, then open the valve connected to the high-purity nitrogen cylinder, and inject nitrogen until the pressure gauge shows 10 6 bar, close the valve connected to the high-purity nitrogen cylinder, and 6 Maintain above bar for 30 minutes.

[0070] Then the anodized aluminum was taken out for PVDF curing, and kept at 70°C for 2 h in a forced air drying oven, and then kept at 130°C for 6 h.

[0071] (4) Corona polarization treatment:

[0072] The cured anodized aluminum was polarized using high-voltage equipment, with a single needle structure, an electric field strength of 7 kV / cm, a voltage of 7 kV, a distance between the needle tip and the anodized aluminum surface of 10 mm, and a polarization time of 30 min.

[0073] like Figure 3 As shown, this is a cross-sectional SEM morphology of the AAO / PVDF composite coating prepared in this embodiment, from which it can be seen that PVDF completely covers the surface of the anodized aluminum AAO, and the entire nanopore is filled with PVDF. Therefore, the method provided by the present invention can realize the preparation of an organic-inorganic interlocking spatial structure.

[0074] like Figure 1 As shown, it is a schematic diagram of the structure of the AAO / PVDF composite coating prepared on the aluminum substrate through the above steps of the present invention, an anodized aluminum AAO frame is formed on the aluminum substrate by anodizing treatment, and then PVDF is filled into the nanopores of AAO by vacuum solution casting and covered on the upper surface of AAO to form a three-layer interlocking structure.

[0075] Example 2

[0076] This embodiment provides a method for preparing an antibacterial and antifouling AAO / PVDF composite coating with an organic-inorganic intercalated spatial structure based on a hard template-soft modification technology. The specific steps are basically the same as those in Example 1, except that:

[0077] (1) A 40 g / L NaOH solution was used in the aluminum alloy pretreatment, the volume ratio of HClO4 and C2H5OH electrolyte was 1:4, and the voltage of electrochemical polishing was 25 V.

[0078] (2) In the corona poling treatment, a 3×3 multi-needle array structure was used as the polarization needle tip, the needle tip spacing was 5 mm, the distance between the needle tip and the anodized aluminum surface was set to 10 mm, the voltage was set to 5 kV, the electric field strength was 5 kV / cm, and the polarization time was 30 min.

[0079] Example 3

[0080] The present embodiment provides a method for preparing an antibacterial and antifouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure based on a hard template-soft modification technology. The specific steps are basically the same as those in Example 2, except that a 3×3 multi-needle array structure is used as a polarization needle tip in the corona poling treatment, the needle tip spacing is 5 mm, the spacing between the needle tip and the anodized aluminum surface is set to 10 mm, the voltage is set to 7 kV, and the electric field strength is 7 kV / cm.

[0081] Example 4

[0082] This embodiment provides a method for preparing an antibacterial and antifouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure based on a hard template-soft modification technology. The specific steps are basically the same as those in Example 3, except that:

[0083] In the corona poling treatment, a 3×3 multi-needle array structure is used as the polarization needle tip, the needle tip spacing is 5 mm, the distance between the needle tip and the anodized aluminum surface is set to 10 mm, the voltage is set to 10 kV, and the electric field strength is 10 kV / cm.

[0084] Comparative Example 1

[0085] The specific steps of this comparative example are basically the same as those of Example 4, except that this comparative example only performs anodizing treatment on the aluminum alloy substrate without subsequent PVDF soft modification process. Only anodized aluminum AAO can be obtained through the preparation method of this comparative example.

[0086] Comparative Example 2

[0087] The specific steps of this comparative example are basically the same as those of Example 4, except that the AAO / PVDF composite coating in this comparative example is not subjected to the high-voltage corona polarization treatment in step 4.

[0088] Comparative Example 3

[0089] The specific steps of this comparative example are basically the same as those of Example 4, except that the aluminum alloy in this comparative example is not anodized, and the PVDF coating is directly prepared on the surface of the aluminum alloy, and then the PVDF coating is also subjected to the same corona polarization treatment as in Example 4.

[0090] Effect Example

[0091] Figure 4 The SEM morphology photos of Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 2, Example 3 and Example 4 are shown in the figure. The labels AAO, A / P-0, Al / P-10, A / P-5, A / P-7 and A / P-10 represent the coatings of Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 2, Example 3 and Example 4 respectively. It can be seen from the figure that the nanopores of AAO are evenly dispersed, the pore size is relatively uniform, and the average pore size is about 40nm. The surface of the A / P-0 coating without polarization treatment is the original morphology of the PVDF coating, and all the nanopores are completely covered. As the polarization electric field increases, the PVDF surface undergoes obvious deformation. When corona polarization is performed at an electric field strength of 5kV / cm, the flocculent amorphous microstructure of PVDF on the surface of the A / P-0 coating is transformed into an elongated silkworm-like crystal domain composed of spherules. When the electric field strength increases to 7kV / cm and 10kV / cm, the surface of the A / P-7 coating presents leaf-like flakes, and the surface of the A / P-10 coating becomes a dense rod-like crystal. The increase in the polarization electric field strength gradually increases the crystallinity of the AAO / PVDF composite coating, and has a significant effect on the piezoelectric properties of the AAO / PVDF composite coating. Comparative Example 3 prepares PVDF on the surface of an aluminum alloy without an anodized aluminum nanoporous structure, so the AAO / PVDF organic-inorganic interlocking spatial structure is not formed, and its surface morphology after applying voltage is also different from that of Example 4.

[0092] Figure 5 The XRD patterns of Comparative Example 2 (A / P-0), Example 2 (A / P-5), Example 3 (A / P-7) and Example 4 (A / P-10) are shown in Table 1. The diffraction peaks at 20.6° are the (110) and (200) diffraction planes of the piezoelectric β-PVDF crystalline phase. Figure 5 It can be seen that the content of piezoelectric β-PVDF crystalline phase increases with the increase of electric field intensity.

[0093] Figure 6 is the piezoelectric coefficient d of Comparative Example 2 (A / P-0), Example 2 (A / P-5), Example 3 (A / P-7) and Example 4 (A / P-10). 33 , as the electric field strength increases from 0kV / cm to 10kV / cm, d 33The average value increased from 4.5pC / N to 31.4pC / N, indicating that with the increase of electric field intensity, the content of piezoelectric β-PVDF crystalline phase increased, which enhanced the piezoelectric properties of AAO / PVDF composite coating.

[0094] Figure 7 The macroscopic photos of the coated plates of planktonic Escherichia coli and Staphylococcus aureus of Comparative Example 1 (AAO), Comparative Example 2 (A / P-0), Example 2 (A / P-5), Example 3 (A / P-7) and Example 4 (A / P-10) show that as the piezoelectric properties of the AAO / PVDF composite coating are enhanced, the planktonic bacterial colonies on the agar plate in the coated plate experiment gradually decrease; Figure 8 The SEM morphology of the adhered Escherichia coli and Staphylococcus aureus of Comparative Example 1 (AAO), Comparative Example 2 (A / P-0), Example 2 (A / P-5), Example 3 (A / P-7) and Example 4 (A / P-10) shows that as the piezoelectric properties of the AAO / PVDF composite coating increase, the number of adhered bacteria decreases gradually, and the structure of the adhered bacteria is significantly deformed. Figure 7 and Figure 8 It can be seen that the A / P-10 coating has the best antibacterial performance, with an antibacterial rate of 99%. The adherent bacteria on the surface have obvious cytoplasm leakage and are in a state of apoptosis.

[0095] Fig. 9 The electrochemical curves of aluminum substrate (Al), comparative example 1 (AAO), comparative example 3 (Al / P-10) and embodiment 4 (A / P-10) are compared and analyzed. The polarization curve comparison between comparative example 1 and aluminum substrate shows that anodizing treatment improves the self-corrosion potential of aluminum alloy, reduces the corrosion current of aluminum alloy, and the AAO layer significantly improves the corrosion resistance of aluminum alloy; at the same time, the polarization curve of comparative example 3 (Al / P-10) proves that PVDF can isolate aluminum alloy from contacting corrosive medium, and the polarization curve at this time is a horizontal line, and the electrode reaction on the surface of the sample is weak; the polarization curve of embodiment 4 (A / P-10) further proves that after PVDF seals the nanopores of AAO, the potentiodynamic polarization curve shows a lower horizontal line feature, and the current density signal at this time has no accurate value, indicating that there is no observable electrode reaction on the surface of AAO / PVDF composite coating, the corrosion resistance of AAO / PVDF composite coating has reached the best state, the aluminum alloy has not been corroded, and the mutually embedded spatial structure between PVDF and AAO completely inhibits the infiltration of corrosive medium.

[0096] In addition, after immersion in 3.5% NaCl solution for 30 days, the aluminum substrate and the surface of comparative example 1 were severely corroded, and the corrosion behavior of comparative example 3 was also relatively obvious, while the AAO / PVDF composite coating of Example 4 still had no obvious corrosion phenomenon, indicating that the PVDF layer on the surface of the aluminum alloy alone cannot isolate the corrosive medium from contacting the aluminum alloy for a long time. Only when PVDF and AAO form a mutually embedded spatial structure can they protect the aluminum alloy from contacting the corrosive medium for a long time, proving that the AAO / PVDF composite coating has long-term corrosion resistance.

[0097] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a long-lasting anticorrosion and antifouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure based on a hard template-soft modification technology, characterized in that: The following steps are involved: S1. Anodizing treatment: Anodizing the aluminum alloy substrate in an electrolyte to obtain an anodized aluminum layer, and then performing pore expansion treatment; S2, vacuum solution casting: vacuum degassing the anodized aluminum layer obtained in step S1, and then fully filling the PVDF solution into the nanopores of the anodized aluminum layer under high-purity nitrogen pressure treatment, and then performing PVDF curing treatment after filling; S3. Corona polarization treatment: The cured anodized aluminum layer is subjected to corona polarization treatment to obtain an AAO / PVDF composite coating having an organic-inorganic intercalated structure with piezoelectric properties.

2. The method according to claim 1, characterized in that In step S2, the vacuum degassing and high-purity nitrogen pressurization steps are performed in a high-pressure tank. During the vacuum degassing, the high-pressure tank is first evacuated to 0-0.1 bar and maintained for 1-2 minutes, and then the PVDF solution is contacted with the anodized aluminum layer at 0-0.1 bar and maintained for 10-60 minutes; high-purity nitrogen is introduced and pressurized to 10 6 -10 7 bar, maintain for 20-60min.

3. The method according to claim 1, characterized in that: In step S2, during the curing treatment, the material is first kept at 60-80°C for 1-3 hours, and then kept at 110-140°C for 3-8 hours.

4. The method according to claim 1, characterized in that In step S1, the aluminum alloy substrate must be pretreated before anodizing, specifically including: grinding, polishing and ultrasonic cleaning the aluminum alloy, then alkaline washing and acid washing, and then electrochemical polishing in a solution containing perchloric acid to obtain an aluminum alloy substrate in a reflective mirror state.

5. The method according to claim 4, characterized in that The alkali solution used for the alkali washing is a 25-40g / L NaOH solution; the acid solution used for the acid washing is a 20-25% by mass HNO3 solution; And / or, the electrochemical polishing is carried out in a perchloric acid / ethanol electrolyte at a DC voltage of 20-25V and a water bath temperature of 0-5°C; in the electrolyte, the volume ratio of perchloric acid to ethanol is 1:3-1:

5.

6. The method according to claim 1, characterized in that In step S1, during the anodizing treatment, the aluminum alloy substrate is used as the anode working electrode, and the inert conductive electrode is used as the cathode. The anodized aluminum alloy is treated at a constant pressure in an acidic electrolyte and a constant temperature water bath for 15-60 minutes; the inert conductive electrode includes at least one of a carbon plate, a titanium plate, a platinum sheet, and a gold sheet; the acidic electrolyte includes at least one of phosphoric acid, sulfuric acid, and oxalic acid solution.

7. The method according to claim 1, characterized in that In step S1, the solution used for the pore expansion treatment is a phosphoric acid solution with a mass fraction of 3-5%, the temperature of the pore expansion treatment is 40-60°C, and the time is 5-30 minutes.

8. The method according to claim 1, characterized in that In step S2, the PVDF solution is prepared by dissolving PVDF powder in an organic solvent, the mass fraction of PVDF in the PVDF solution is 30-70%, and the organic solvent is N,N-dimethylformamide.

9. The method according to claim 1, characterized in that: In step S3, during the corona polarization treatment, the electric field strength is 3-20 kV / cm, the voltage is 4-20 kV, the distance between the needle tip and the anodized aluminum surface is 3-15 mm, and the treatment time is 30-60 min.

10. A long-lasting anti-corrosion and anti-fouling AAO / PVDF composite coating with an organic-inorganic interlocking spatial structure, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A kind of method for preparing polyvinylidene fluoride nano-array porous membrane

    CN104959045B

  • Preparation method of aluminum alloy super-hydrophobic membrane with anti-corrosion, anti-fouling and self-repairing functions

    CN118773698A

  • Preparation method of piezoelectric antibacterial and antifouling film layer on surface of maritime work metal material

    CN114907729A

  • Aluminum alloy plate for outdoor building and coating process of aluminum alloy plate

    CN117822794A

  • Ferroelectric fine structure, its manufacturing method and recording reproducing method

    JP2005118936A

Cited By

  • Preparation method of magnesium alloy stent composite coating

    CN121971704A